Health risk behaviors among male students in secondary schools in Erbil city - ALhag Baker, Jawdat Mamand; Al-Doski, Nazar Ali shreen (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Health behaviors and risk behaviors are often related to the community in a more complex pattern of behaviors associated with lifestyles. Risk behaviors include drinking alcohol, physical fighting, smoking, sexual intercourse and drug abuse. This study aimed to assess the rates of some health risk behaviors among male students of secondary schools in Erbil city and to find out associated factors with those risk behaviors. Methods: A cross-sectional study was used. A self-administer questionnaire was used to collected data from December 17th, 2012 to July 17th, 2013 in 12 male secondary schools. 500 students were chosen randomly out of 11343 males’ secondary school students. Results: Smoking was the most common risk behavior among the students (41.7%), followed by physical fighting (33.3%), sexual intercourse (15.5%), alcohol drinking (6.6%), and the lowest risk behaviors comes from drug abuse (2.7%). There was significant association between age and drug abuse which was more common among those ≥21 years than those of younger age groups. Conclusion: The highest health risk behavior among all male students in secondary schools in Erbil city was cigarette smoking. There was statistically significant association between age and drug abuse.